A polissemia da noção de competência no campo da educação (Revista de Educação Pública, 2012)
A partir de exame de concepções teóricas que utilizam o termo competência procura-se demonstrar que, ao associar competência, empregabilidade e profissionalização, o discurso subordina a educação e conceitos oriundos da psicologia educacional às demandas socioeconômicas dos novos modelos de articulação produtiva, além de revelar uma compreensão do sujeito de forma idealizada e não situada. Questões sobre formação e trabalho, de caráter social, são transferidas para a esfera do sujeito, por meio da psicologização da competência, escondendo contradições e desafios a serem enfrentados pelo setor educacional, especialmente na formação docente.The polysemy of the notion of competence in the field of educationAbstractStarting from the review of theoretical conceptions that use the term competence, we try to demonstrate that, by associating competence, employability and professionalization, the speech subordinates education and concepts originating from educational psychology to the socioeconomic demands of new models of productive articulation, in addition to revealing an understanding of the subject in idealized and not situated manner. Questions on education and work, of social nature, are transferred to the scope of the subject, through the psychologization of competence, hiding contradictions and challenges to be faced by the educational sector, particularly in the teacher educationKeywords: Competence. Education and work. Educational assessment.